PENGARUH MEKANISME CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR GO PUBLIK DI INDONESIA - Dio Nuary Rifada, 12.05.52.0142; Alfasadun, Alfasadun (Students Journal of Accounting and Banking, 2016)
This study is the test and analyze the effect of the audit committee, independent board, managerial ownership and profitability on earnings management in manufacturing companies that go public in Indonesia. The population in this research is manufacturing companies listed in Indonesia Stock Exchange 2013-2015 period. The procedure used to determine the research sample is purposive sampling method sampling technique with a certain considerations. According to predetermined criteria there are 43 companies sampled. The analysis technique used is multiple linear regression. Based on the test results it can be concluded that the audit committee has a significant negative effect on earnings management. Independent board and no significant negative effect on earnings management. Managerial ownership and significant negative effect on earnings management. Profitability is not a significant positive effect on earnings management.Â Â Keywords:Â Audit Committee, Independent Board, Managerial Ownership, Profitability and Earnings Management